2018
DOI: 10.3390/urbansci2030066
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Comfortable Summertime Indoor Temperatures by Means of Passive Design Measures to Mitigate the Urban Heat Island Effect—A Sensitivity Analysis for Residential Buildings in the City of Vienna

Abstract: The waste heat generated from the use of air conditioning systems in cities significantly contributes to the urban heat island effect (UHI) during the summer months. Thus, one of the key measures to mitigate this effect is to limit the use of active cooling systems. In the city of Vienna, air conditioning units are common in nonresidential buildings, but have so far been much less installed in residential buildings. This is mainly due to the fact that the Viennese summertime climate is still considered to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
2
17
0
2
Order By: Relevance
“…The use of air conditioners, however, also increases energy consumption [1,8]. Due to the exhaust heat from an air conditioner's outdoor unit, this could contribute to climate change and could actually raise the outdoor temperature [3,26,27]. During the night, this phenomenon is particularly strong, reducing the building's ability to cool [3,28].…”
Section: Causes Of Uhi In Tropical and Global Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of air conditioners, however, also increases energy consumption [1,8]. Due to the exhaust heat from an air conditioner's outdoor unit, this could contribute to climate change and could actually raise the outdoor temperature [3,26,27]. During the night, this phenomenon is particularly strong, reducing the building's ability to cool [3,28].…”
Section: Causes Of Uhi In Tropical and Global Citiesmentioning
confidence: 99%
“…Researchers in Vienna are investigating the use of "plus-energy" and modern smart buildings, capable of generating, storing, and using energy conveniently within a building's constraints, which will provide more efficient and economical solutions [27]. Architectural solutions include external shading, ventilation at night, and a large thermal mass of construction materials.…”
Section: Green Facadementioning
confidence: 99%
“…In order to avoid this additional heat burden, the city of Vienna has published recommendations for planners to avoid summertime overheating by implementing adequate passive design measures into their building designs. Simulations with future climate data have shown that in residential buildings, air conditioning can be avoided with a combination of high thermal mass, shading, and night cooling [12].…”
Section: Period Frost Days Ice Days Summer Days Heat Daysmentioning
confidence: 99%
“…Much research has set out to establish the risk of overheating by simulating the current and future risk in older dwellings [18] and in newer dwellings [19] in different countries around the world. A number of studies have also demonstrated present-day monitored overheating or summer 'discomfort' in existing dwellings and newly built dwellings [12,[20][21][22][23] in the UK and abroad, in Denmark [24], Austria [25], Sweden [26], and Estonia [27]. Within these studies the propensity to overheat is much greater in newer dwellings, e.g., Passivhaus designed dwellings, and particularly in flats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overheating can occur in homes as a result of several causes acting alone or together. These include heat gain from high external temperatures [36], higher localised temperatures exacerbated by the urban heat island (UHI) effect [25], direct solar gain on the exterior surface or penetrating glazing, and internal heat gains. Home characteristics such as dark surface materials, rooms in the roof, skylights, inability to ventilate due to location, predominately dark hard surface surroundings, single aspect flats on upper floors [37], and orientation that allows late solar gain in windows can all contribute to overheating [13].…”
Section: Literature Reviewmentioning
confidence: 99%